The Effect of Students' Daily Tasks on The Formation of Independence In Fifth Grade Elementary School Students - Delia Nurul Fauziah; Sapriya; Effy Mulyasari; Muhammad Gilang Hendrawan (International Conference on Elementary Education, 2025)
Elementary students' independence remains a persistent challenge, as many continue to rely heavily on teachers and parents when completing daily tasks. This study aims to analyze how daily assignments contribute to the development of independence among fifth-grade students in a public elementary school in Bandung. Employing a qualitative descriptive approach, the study involved oneclass as the research subject. Data were gathered through questionnaires, classroom observations, and documentation to obtain a comprehensive and contextual understanding of students’ independent learning behaviors. The findings show that systematically implemented daily tasks fostered significant improvements in responsibility, self-discipline, persistence, and confidence in completing work without excessive support. Students gradually demonstrated greater initiative in preparing learning materials, managing their routines, and making simple decisions during classroom activities. Field notes also highlight that clear teacher instructions and the trust given to students played essential roles in supporting the emergence of independent learning. Overall, the study indicates that daily assignments function not only as routine activities but also as an effective pedagogical strategy to strengthen independence as an important character value in elementary school students